Beyond searching : user's cognizance of electronic journals. - Geh, Beng Juah. (2008)
The main objective of the study was to determine the use and perception of electronic journals by graduate students in the School of Communication and Information (SCI) in Nanyang Technological University (Singapore). This study involved the exploration of cognizance, that is, knowledge of use and perception, of electronic journals.